Interpretation of Love in the Book of Sajak Nun by Abdul Wachid B. S. (Riffatere Semiotic Analysis) - Rahayu, Tania (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
This poetry analysis was made with the aim of interpreting the concept of love in the book 'Collection of Nun Rhymes' by Abdul Wachid B. S. This qualitative research uses literature research methods. Data collection is carried out using reading and recording techniques both lecture notes, books, journals and literature related to the discussion in research. The selected poems that were used as the object of this study were poems entitled 'Lap of the Heart' and 'I Tear' in the book 'Collection of Nun Rhymes'. Dissection of the meaning of poetry applies Michael Riffaterre's semiotic theory relating to Huristic and Hermeneutic approaches, Models, Variants and Matrices and HypogramsAnalisis puisi ini dibuat dengan tujuan untuk menginterpretasikan konsep cinta dalam buku ‘Kumpulan Sajak Nun’ karya Abdul Wachid B. S. Penelitian kualitatif ini menggunakan metode penelitian kepustakaan. Pengumpulan data dilakukan dengan menggunakan teknik baca dan catat baik catatan kuliah, buku, jurnal serta literatur yang berkaitan dengan pembahasan pada penelitian. Puisi-puisi pilihan yang dijadikan objek penelitian ini merupakan puisi berjudul ‘Pangkuan Hati’ dan ‘Aku Airmata’ dala buku ‘Kumpulan Sajak Nun’. Pembedahan makna puisi menerapkan teori semiotik Michael Riffaterre yang berkaitan dengan pendekatan Huristik dan Hermeneutik, Model, Varian dan Matriks serta Hipogram.